How to end a love story : a novel [large type] - Kuang, Yulin (Thorndike Press large print romance series., 2024)
Helen Zhang hasn't seen Grant Shepard once in the thirteen years since the tragic accident that bound their lives together forever. Now she's in Los Angeles, where the two have to work together. The result is messy, and electrifying.